Characteristics and Risk Factors of Postoperative Complications in Gastric Cancer Patients Treated with Neoadjuvant Chemotherapy - SUN Chongyuan (Magazine House of Cancer Research on Prevention and Treatment, 2021)
Despite the continuous development of medical devices and the standardization of gastrectomy plus D2 lymph node dissection, advanced gastric cancer still has high distant metastasis rate and local recurrence rate, and the prognosis is poor. Neoadjuvant chemotherapy can improve the long-term survival of patients with advanced gastric cancer by reducing tumor stage, increasing R0 resection rate and eliminating potential micrometastasis. However, it is still the focus of concern that whether the adverse reactions of preoperative chemotherapy will increase the incidence of postoperative complications. Postoperative complications can affect the oncological outcomes by activating minimal residual lesions and promoting metastasis through related inflammatory changes or delaying adjuvant therapy, so the premise of wide application of neoadjuvant chemotherapy should be the guarantee of surgical safety. This article reviews the incidence, severity and prognosis of operative complications in gastric cancer patients after neoadjuvant chemotherapy and further explores its influencing factors.